A Review of the Quality Improvement in Discharge Planning through Coaching in Nursing - Rahayu, Candra Dewi; Hartiti, Tri; Rofiâ€™i, Muhamad (Nurse Media Journal of Nursing, 2016)
Background: Discharge planning quality will improve the quality of nursing care, patientâ€™s self-reliance, quality of life, self-efficacy, and reduce the recurrence rate andLOS (Length of Stay) as well as reduce the cost. Coaching is a method to increase professionalism in the delivery of nursing and caring. Coaching in nursing will improve the nursesâ€™ skills, knowledge, and motivation in providing nursing discharge planning.Purpose: The study aimed to review coaching in nursing to improve the quality of discharge planning.Methods: A literature review was done by collecting the results of scientific publications within 2011-2016 from databases such as EBSCO, ProQuest, PubMed,Google scholar, and the American Journal of Nursing (AJN). Searching was done using the keywords of â€œcoachingâ€, â€œnurseâ€, â€œsupervisionâ€ and â€œdischarge planningâ€.Results: Six scientific publications were selected in accordance with the criteria of this research. Those publications were of quantitative correlation, experimental and qualitative studies. Results of the review showed that the discharge planning is part of nursing care. Coaching is a competence which must be possessed by nursing managers.Unfortunately, the majority of managers were still lacking in their ability to conduct coaching to nurses.Conclusion: Coaching is important for nurses to improve the quality of discharge planning. However, many nurses still have limitation on their capability to do coaching. It is recommended that nurses are given coaching trainingÂ to develop their ability in coaching.